A Study on Psychological Stress Among The Players of Various Games - Naveen Kumar Bhardwaj (Eduzone: International Peer Reviewed/Refereed Multidisciplinary Journal, 2013)
Stressors have a major influence upon mood, our sense of well-being, behavior, and health. Intense pressure reactions in youthful, solid people might be versatile and ordinarily don't force a wellbeing trouble. Notwithstanding, on the off chance that the danger is unremitting, especially in more seasoned or unfortunate people, the drawn out impacts of stressors can harm wellbeing.